Identifikasi Miskonsepsi Peserta Didik Menggunakan Two-Tier Test Berbantuan Certainty Of Response Index : (Misconception Identification of Students using Two-Tier Test Assisted by Certainty of Response Index) - Herfine Fristiansa Firman; Jujun Ratnasari; Sistiana Windyariani (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2021)
The misconception is a problem in learning and it is very necessary to solve it so that learning is better. Students who are identified with misconceptions on material concepts can make it difficult for them to believe new concepts that are true. The purpose of this study is to identify the existence of misconceptions in students in an ecosystem material concept that they have studied previously. This study uses a descriptive method with a quatitative approach. The research was conducted at Senior High School (SMA) in Sukabumi Regency. The subjects studied were 36 students of class XI MIPA 5. The instrument used was 45 multiple choice questions with the help of the Certainty of Response Index (CRI). The results showed the understanding of students in the percentage of conceptual understanding (PK), understanding the concept of being unsure (PKKY), Misconception (M), and not knowing the concept (TTK) were 20%, 6%, 32%, 42%. The highest misconception percentage at level 1 after testing was at the indicator describing the relationship between ecosystem components (60%), level 2 understanding the pattern of interactions between organisms (53%), and the lowest on indicators showing succession definition (12%). Therefore, misconceptions among students in ecosystem material need to be eliminated by choosing the right method, learning model, and approach. Abstrak. Miskonsepsi merupakan permasalahan di dalam pembelajaran dan sangat perlu dilakukan penyelesaian agar suatu pembelajaran lebih baik. Peserta didik yang teridentifikasi miskonsepsi pada suatu konsep materi dapat membuat mereka sulit dalam mempercayai konsep baru yang benar. Tujuan dari penelitian ini yaitu untuk mengidentifikasi adanya miskonsepsi pada peserta didik dalam suatu konsep materi ekosistem yang telah mereka pelajari sebelumnya. Penelitian ini menggunakan metode deskriptif dengan pendekatan kuantitatif. Penelitian dilakukan di Sekolah Menengah Atas (SMA) yang berada di Kabupaten Sukabumi. Subjek yang di teliti merupakan 36 peserta didik kelas XI MIPA 5. Instrumen yang digunakan berupa 45 soal pilihan ganda beralasan berbantuan Certainty of Respon Index (CRI). Hasil penelitian menunjukan pemahaman peserta didik dalam persentase paham konsep (PK), paham konsep kurang yakin (PKKY), Miskonsepsi (M) dan Tidak tahu konsep (TTK) adalah 20%, 6%, 32%, 42%. Perolehan persentase miskonsepsi tertinggi pada level 1 setelah pengujian berada pada indikator mendeskripsikan hubungan antar komponen ekosistem (60%), level 2 memahami pola interaksi antar organisme (53%) dan terendah pada indikator menunjukan devinisi suksesi (12%). Maka dari itu miskonsepsi pada peserta didik dalam materi ekosistem perlu dihilangkan dengan memilih metode, model pembelajaran dan pendekatan yang tepat.